Peningkatan Kesadaran Pendidikan Tinggi melalui Kolaborasi Perguruan Tinggi: Implementasi Aplikasi 'Jamali Parenting' di Desa Jamali, Cianjur : Increasing Higher Education Awareness through Higher Education Collaboration: Implementation of the 'Jamali Parenting' Application in Jamali Village Cianjur - Fitrianingsih, Fitrianingsih; Saryoko, Andi; Elyana, Instianti; Aziz, Faruq; Ramadhan, Aditya Rian; Supriyono, Lawrence Adi; Andini, Siwi Putri; Budiyanto, Sarah Khairunnisa; Daryati, Elisabeth Isti; Wadu, Novita M Kana; Erna, Maria Agustina; Dwiyogo, Santos Winarso; Saeda, Ida (Sam Ratulangi University, 2024)
This Community Service Activity is a collaboration of five universities under the auspices of LLDIKTI III, namely Gunadarma University, Nusa Mandiri University, Jakarta International University, Esa Unggul University, and STIK Sint Carolus. This activity aims to increase public awareness of the importance of higher education in building the future of the golden generation. The event was held on Monday, December 9, 2024, at the Jamali Village Hall, Mande District, Cianjur Regency, West Java, with the partner of the Head of Jamali Village, Mr. Cece Rusman, S.IP. Activities include outreach regarding parenting patterns for child growth and development and the importance of higher education as the key to the future of the golden generation. In addition to education, this activity resulted in an innovation in the form of the